2012
DOI: 10.1002/anie.201204930
|View full text |Cite
|
Sign up to set email alerts
|

Hard X‐ray Nanotomography of Catalytic Solids at Work

Abstract: The authors acknowledge financial support from The Dow Chemical Company. The Stanford Synchrotron Radiation Lightsource (SSRL) is supported by the US Department of Energy, Office of Basic Energy Sciences. We wish to thank to A. van der Eerden (Utrecht University) for his help with the design of the reactor cell. We further acknowledge P. Williams and T. Kao (SSRL) for their help during the data processing and R. Marks (SSRL) for the setting up of the gas flow system.Supporting information for this article is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 98 publications
(64 citation statements)
references
References 31 publications
0
63
0
Order By: Relevance
“…X-ray absorption near edge structure (XANES) has provided a new insight into chemical environment of biominerals and mineralised tissues [25][26][27][28][29][30].While XAS studies provide a very high energy resolution, the spatial resolution is not adequate to resolve features below 15nm [31][32][33]. Although the average sized crystal platelets (100nm long, 50nm wide, 5nm thick [34,35]) could be examined, investigation of smaller (5-10nm) features such as intercrystal spaces, grain boundaries and protein-mineral interfaces is below the spatial resolution limit of XAS.…”
Section: Introductionmentioning
confidence: 99%
“…X-ray absorption near edge structure (XANES) has provided a new insight into chemical environment of biominerals and mineralised tissues [25][26][27][28][29][30].While XAS studies provide a very high energy resolution, the spatial resolution is not adequate to resolve features below 15nm [31][32][33]. Although the average sized crystal platelets (100nm long, 50nm wide, 5nm thick [34,35]) could be examined, investigation of smaller (5-10nm) features such as intercrystal spaces, grain boundaries and protein-mineral interfaces is below the spatial resolution limit of XAS.…”
Section: Introductionmentioning
confidence: 99%
“…46 The latter report showed that hard X-ray TXM is particularly suited to the study of hierarchical structures in functional materials such as battery electrodes due to the strong X-ray penetration and depth of focus, enabling the study of large areas in 2D and 3D. 4749 …”
Section: Introductionmentioning
confidence: 99%
“…HP-XPS (highpressure X-ray spectroscopy), EXAFS (extended X-ray absorption fine structure) and NEXAFS (near edge X-ray absorption fine structures) spectroscopy measurements detect the oxidation state, coordination number, and composition of catalysts [45,46]. High spatial resolution XRD (X-ray diffraction) and EXAFS microspectroscopy along with X-ray tomography measurements tracked the dynamic changes in the structure and composition of catalysts [47][48][49][50]. These in situ measurements demonstrated that the catalytic surface is dynamic and its structure, composition, and electronic properties can be widely modified under reaction conditions.…”
Section: Advanced Instrumentation For In Situ Characterization Of Catmentioning
confidence: 99%